Pengaruh Harga, Kualitas Produk dan Kepercayaan terhadap Keputusan Pembelian Fashion Secara Online pada Mahasiswa Pendidikan Ekonomi, Universitas Pendidikan Ganesha - Supraeni, Ni Luh; Suwendra, I Wayan (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
The purpose of this research is to determine (1) the influence of price on online fashion purchasing decisions (2) the influence of product quality on online fashion purchasing decisions (3) the influence of trust on online fashion purchasing decisions, (4) the influence of price, product quality and confidence in online fashion purchasing decisions. The type of research used is causal research. The sampling technique used is simple random sampling. The population of this research is Economics Education Students Class of 2021 and 2022, with a sample size of 122. The data collection method uses a questionnaire and is analyzed using multiple linear regression, which includes the t test (T-test). The research results show that (1) there is a positive and significant influence of price on online fashion purchasing decisions partially, with a significance value of 0.000 <0.05. (2) there is a positive and significant effect of product quality on online fashion purchasing decisions partially, with a significance value of 0.000 <0.05. (3) there is a positive and significant influence of trust on online fashion purchasing decisions partially, with a significance value of 0.000 <0.05. (4) There is a positive and significant influence between price, product quality and trust on online fashion purchasing decisions simultaneously, with a significance value of 0.000 <0.05. The magnitude of the influence of price, product quality and trust on purchasing decisions is equal to 25.9%, evidenced by a coefficient of determination of 0.259.